The impact of parenting styles on undergraduate students’ emotion regulation: The mediating role of academic-social student-faculty interaction - Yao, Hao; Chen, Shuzhen; Gu, Xiulin (Frontiers in Psychology, 2022)
Based on the survey data of 4462 undergraduate students in Zhejiang Province, mainland China, this study investigated the influence of parenting styles on emotion regulation and the mediating role of student-faculty interaction. The study found that: (1) Male students scored significantly higher than female students on emotion regulation, overprotective parenting style and student-faculty interaction. (2) Parenting style has a direct positive effect on emotion regulation, and warm parenting style has a much greater effect on emotion regulation than overprotective parenting style. (3) The mediating effect of student-faculty interaction in the relationship between parenting style and emotion regulation holds true, with the mediating effect of academic student-faculty interaction being much higher than that of social student-faculty interaction. (4) The influence of warm parenting style on emotion regulation relies more on the direct effect, while the influence of overprotective parenting style on emotion regulation relies more on the mediating effect of student-faculty interaction.